2014
DOI: 10.1021/ie403993c
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Polymer Coating/Encapsulation of Submicrometer Particles Using a Solid Hollow Fiber Cooling Crystallization Method

Abstract: Currently, no technique is available to continuously film coat nanosized drug particles with a polymer to produce large amounts of free-flowing coated particles. In this work, Eudragit RL 100 and poly(d,l-lactide-co-glycolide) (PLGA) were chosen as the coating polymers and Cosmo 55 (550 nm silica particles) as a surrogate for drug particles. After determining the cloud point of the polymer solutions by UV spectrophotometry, we adopted the solid hollow fiber cooling crystallization (SHFCC) technique to continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…An evaluation of the crystalline products from the device outlet suggests that the drug crystallized first; the polymer precipitated later and covered the pre-existing drug crystals and the new drug crystals formed. Our earlier studies (Chen et al, 2014a;Chen et al, 2014b;Chen et al, 2015) have shown that Eudragit precipitation is a somewhat slow process regardless of the precipitation technique employed. No free uncoated crystals were visible.…”
Section: Coating Of Griseofulvin Drug Particles With Eudragit Polymer In the Shfcc Unitmentioning
confidence: 93%
See 3 more Smart Citations
“…An evaluation of the crystalline products from the device outlet suggests that the drug crystallized first; the polymer precipitated later and covered the pre-existing drug crystals and the new drug crystals formed. Our earlier studies (Chen et al, 2014a;Chen et al, 2014b;Chen et al, 2015) have shown that Eudragit precipitation is a somewhat slow process regardless of the precipitation technique employed. No free uncoated crystals were visible.…”
Section: Coating Of Griseofulvin Drug Particles With Eudragit Polymer In the Shfcc Unitmentioning
confidence: 93%
“…Details of the relation between cloud point temperature and the ratio of acetone/water are provided in Chen et al (2014a). A cloud point temperature of 15 o C was selected; it is easily achieved in the laboratory for cooling crystallization experiments; correspondingly, the ratio of acetone/water in ml/ml for this cloud point was 2.5/0.5.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[186] One of the main issues in the controlled drug delivery systems is the initial burst release. There are some strategies applied to the coating procedure, which can help to achieve sustained release over time, such as using microcapsules and adhesives drugs that can adhere to biological tissues for an extended period of time, [183,187] repeated layers of drug coating on fibers using L-B-L deposition, [188] or taking advantage of processes, such as ultrasound, ion-beam, and irradiation. [4,28,189] For instance, Ma et al [183] coated cotton fabrics with a solution comprised of tamoxifen drug microencapsulated in gelatin B and acacia gum as an anti-cancer drug for the treatment of breast cancer.…”
Section: Coatingmentioning
confidence: 99%